THE ANALYSIS OF LEADERSHIP CHARACTER OF SNOW QUEEN OF ARENDELLE IN DISNEY MOVIE â€œFROZENâ€ - Soares, Geralda A. Lay X. F. (Apollo Project: Jurnal Ilmiah Program Studi Sastra Inggris, 2019)
Animated movie "Frozen" tells the story of the adventures of a girl named Anna and her friends against Snow Queen. Snow Queen act coused, freezing in the whole empire and the people suffer from the cold. Snow Queen is actually annaâ€™s sister named Elsa. However, in this story is not to discuss about the adventures of Anna against her sister Elsa, but will discuss the character of Elsa. Character is a person depicted in a narrative or drama. Elsaâ€™s character as a princess of the kingdom in Arendelle is a authoritative, loving, coward and insecure. But on the other hand, as the Snow Queen character she was variably, she is assertive and daring. we know that the attitude and character are very important to describe a certain person, if someone does not have the character that he just became him, nobody. A leader should have the attitude and character of it own self to lead the group, nation or kingdom so that the people in the country or the kingdom prosper.